(untitled) - Keshav, S. (Massachusetts, 1997)
Network introduction; The telephone network; The internet; ATM networks; Protocol layer; system design; Multiple access; Switching; Scheduling; Naming and addressing; Routing; Error control; Flow control; Traffic management; Common protocols; Protocol implementation.
Keywords: Hệ thống điện thoại,Telephone systems